Modified coke breeze distribution in iron ore sintering - a novel technique of reducing energy consumption and improving quality - Pal J.; Prasad D.; Venugopalan T. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In normal sintering of iron ore, there is a wide difference in temperature of the sinter bed between top and bottom; i.e. the flame front temperature of the sinter bed gradually increases towards the bottom because the lower part gets longer time for drying and preheating by exit gas. Therefore, the top part may have insufficient fusion and the bottom is excessively fused. Thus, sinter quality may become inhomogeneous and the coke breeze requirement becomes higher than the actual thermal requirement. If it is charged in multiple layers; e.g. higher amount of coke at the top and a lower amount of coke at the bottom, heat will be homogeneously distributed and the actual coke requirement would be lower than the existing. However, no study has been done so far on this. Therefore, the current study explores the possibility of reducing energy consumption in iron ore sintering by reducing the coke ratio from top to bottom without deteriorating the sinter property. 12% reduction in coke breeze rate has been found and the sinter quality has been improved by the use of a triple layer of sinter mix with a lower coke rate towards the bottom. Further, when 5-vol% of oxygen has been enriched in suction gas along with using a triple layer of sinter mix, up to an 18-wt% reduction in coke breeze has been found.